AtTrm5a catalyses 1-methylguanosine and 1-methylinosine formation on tRNAs and is important for vegetative and reproductive growth in Arabidopsis thaliana. Issue 2 (1st December 2018) - Jin, Xiaohuan; Lv, Zhengyi; Gao, Junbao; Zhang, Rui; Zheng, Ting; Yin, Ping; Li, Dongqin; Peng, Liangcai; Cao, Xintao; Qin, Yan; Persson, Staffan; Zheng, Bo; et al.
Abstract: Modified nucleosides on tRNA are critical for decoding processes and protein translation. tRNAs can be modified through 1-methylguanosine (m 1 G) on position 37; a function mediated by Trm5 homologs. We show that AtTRM5a (At3g56120) is a Trm5 ortholog in Arabidopsis thaliana . AtTrm5a is localized to the nucleus and its function for m 1 G and m 1 I methylation was confirmed by mutant analysis, yeast complementation, m 1 G nucleoside level on single tRNA, and tRNA in vitro methylation. Arabidopsis attrm5a mutants were dwarfed and had short filaments, which led to reduced seed setting. Proteomics data indicated differences in the abundance of proteins involved in photosynthesis, ribosome biogenesis, oxidative phosphorylation and calcium signalling. Levels of phytohormone auxin and jasmonate were reduced in attrm5a mutant, as well as expression levels of genes involved in flowering, shoot apex cell fate determination, and hormone synthesis and signalling. Taken together, loss-of-function of AtTrm5a impaired m 1 G and m 1 I methylation and led to aberrant protein translation, disturbed hormone homeostasis and developmental defects in Arabidopsis plants.